Beyond words: Outreach and science education for Generation Alpha - Gabriel, Daniela (2024)
In the last decades, there has been an increase in science education out of the school grounds, as well as growing interactions between researchers and the general public in outreach actions. In this regard, it is important to turn science into something meaningful to the non-academic public, and even involve them in data collection. The communication of science to elementary and middle schoolers is becoming more challenging as the age gap between children and researchers grows. Besides, Gen Alpha are usually born in small families, with increasingly less contact with their piers out of school and sport clubs, being somewhat resistant to exploratory or non-routine activities. One approach to reach this public is to take them out of the classroom, letting them make and answer questions as they observe the subjects. To engage in a successful communication, one needs to learn their “language” and be able to make comparisons with games, songs, and choreography they know and like. Another approach is to use games, from adapting simple board games to creating interactive games with virtual reality. Ultimately, the goal is to pass a message so simple and interesting that they easily and eagerly communicate it further to friends and family.